KONSEP KEWENANGAN DALAM PERSPEKTIF HUKUM PERDATA - Zamroni, Mohammad (Mimbar Hukum, 2024)
Abstract Authority is generally always based on attribution, delegation, and mandate, which are sources of authority in administrative law. The concept of authority does originate from administrative law, but the concept of authority is also known and used in the scope of civil law. The problem is that the theory of authority from the perspective of administrative law is often applied in the scope of civil law, despite the difference in subject and object of authority. So, there is a logical fallacy and discrepancy. This research aims to analyze the concept of authority from the perspective of civil law and compare it with the concept of authority from the perspective of administrative law. The approaches used in this research are the statutory approach and the conceptual approach. The results of this research found that authority from the perspective of civil law, in addition to being obtained through attribution, delegation, and mandate, can also be obtained naturally and artificially through contracts, articles of association, power of attorney, and zaakwaarneming. Abstrak Pada umumnya kewenangan selalu disandarkan pada atribusi, delegasi, dan mandat, yang merupakan sumber kewenangan dalam hukum administrasi. Konsep kewenangan memang berasal dari hukum administrasi, tetapi konsep kewenangan juga dikenal dan digunakan dalam lingkup hukum perdata. Permasalahan adalah teori kewenangan dalam perspektif hukum administrasi seringkali diterapkan dalam lingkup hukum perdata, padahal subjek dan objek kewenangannya berbeda. Akibatnya, terjadi kesesatan logika dan diskrepansi. Penelitian ini bertujuan untuk menganalisis konsep kewenangan dalam perspektif hukum perdata, dan membandingkannya dengan konsep kewenangan dalam perspektif hukum administrasi. Pendekatan yang digunakan dalam penelitian ini ialah pendekatan perundang-undangan dan pendekatan konseptual. Hasil dari penelitian ini menemukan bahwa kewenangan dalam perspektif hukum perdata, selain diperoleh melalui atribusi, delegasi, dan mandat, juga dapat diperoleh secara natural dan juga secara artifisial melalui perjanjian, anggaran dasar, surat kuasa, dan zaakwaarneming.